2016
DOI: 10.1007/s11596-016-1652-1
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids increase mechanosensitivity of trigeminal ganglion neurons innervating the inner walls of rat anterior chambers via activation of TRPA1

Abstract: Our previous study found that some trigeminal ganglion (TG) nerve endings in the inner walls of rat anterior chambers were mechanosensitive, and transient receptor potential ankyrin 1 (TRPA1) was an essential mechanosensitive channel in the membrane. To address the effect of cannabinoids on the mechanosensitive TG nerve endings in the inner walls of anterior chambers of rat eye, we investigated the effect of the (R)-(+)-WIN55, 212-2 mesylate salt (WIN), a synthetic cannabinoid on their cell bodies in vitro. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[6][7][8] Our previous studies proved that mechanosensitive TG nerve endings innervate the inner wall of the anterior eye chamber (IWAEC), where aqueous circulation takes place, and that the transient receptor potential ankyrin-1 (TRPA1) is an essential mechanosensitive channel in the membranes of the TG nerve endings. [9][10][11] These results gave a possible answer as to how IOP variation triggers action potentials of the TG nerve. We proposed that mechanosensitive TG nerve endings might act as IOP baroreceptors in neural regulation of the IOP.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…[6][7][8] Our previous studies proved that mechanosensitive TG nerve endings innervate the inner wall of the anterior eye chamber (IWAEC), where aqueous circulation takes place, and that the transient receptor potential ankyrin-1 (TRPA1) is an essential mechanosensitive channel in the membranes of the TG nerve endings. [9][10][11] These results gave a possible answer as to how IOP variation triggers action potentials of the TG nerve. We proposed that mechanosensitive TG nerve endings might act as IOP baroreceptors in neural regulation of the IOP.…”
Section: Discussionmentioning
confidence: 78%
“…30 Intriguingly, our recent study indicated that some TG nerve endings innervating the IWAEC are also mechanically sensitive, and that TRPA1 is an important mechanotransducer in the membrane. [9][10][11] Accumulating evidence has shown that mechanosensitive TG nerve endings in the IWAEC may play a role in IOP sensing. [6][7][8][9][10][11]31,32 Previously, we did not know how an acute IOP elevation could evoke serious eye pain with an ipsilateral headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations